(3GJLGgGJ MOjK aj JOQjS GdJQHjI GdHOfjI h GdQjGVIs - (3GdSGjM eMeO eUWais ((3GdGScfOQjIs (3ecJHI GdGTYGY GdafjIs, 2001)
(3d Y (B810 (3JWQb deNJda YedjGJ h CSGdjH GdJOQjS GdQjGVjI ,h CfhGY GdcaGAGJ GdJOQjHjI ebOeG GSJQGJjLjGJ GdJOQjS h VQhQI GMJQGe GdhbJ GdCcGOjej ddJYdje aj GdJQHjI GdQjGVjI h GSJNOGe GdJbhje dGNJHGQ GdeYdejf(B.s
Keywords: (3GdJQHjI GdHOfjI (B_(3WQb GdJOQjSs